The relationship between the Dark Triad and bullying among Chinese adolescents: the role of social exclusion and sense of control - Huang, Yongqi; Gan, Xiong; Jin, Xin; Rao, Shijie; Guo, Binbin; He, Zijian; Wei, Zixu (Frontiers in Psychology, 2023)
Abundant evidence has proved the association between the Dark Triad and bullying. However, the underlying mechanisms of this relation are still under-investigated. Grounded in the temporal need-threat model, three studies were designed to explore the mediating role of social exclusion and sense of control in this research. Study 1 (N = 571) shows that social exclusion and sense of control would mediate the serial between the Dark Triad and bullying (except social exclusion as a mediator between the Dark Triad and cyberbullying). Study 2 (N = 88) and 3 (N = 102) show that adolescents with high dark triad show lower sense of control and more bullying behavior after experiencing social exclusion. These findings extend the research on the Dark Triad and bullying by providing a solid empirical foundation and intervention strategies to avoid bullying so that the problem can be rationally and scientifically approached.